(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
Human-centered cloud artificial intelligence (AI) collaboration models are transforming modern digital enterprises by integrating human intelligence, cloud computing, machine learning, and collaborative automation into sustainable and secure innovation ecosystems. Enterprises increasingly adopt cloud AI systems to improve operational efficiency, enhance decision-making, strengthen cybersecurity, and support sustainable digital transformation. However, the rapid expansion of AI-driven cloud infrastructures also raises challenges concerning ethics, privacy, transparency, trust, workforce adaptation, governance, and environmental sustainability. Human-centered AI emphasizes the integration of human values, explainability, collaboration, and accountability into intelligent systems to ensure that technological innovation aligns with organizational and societal needs. This study examines the role of human-centered cloud AI collaboration frameworks in enabling secure and sustainable enterprise innovation. The paper explores the theoretical foundations of human-AI collaboration, cloud-native architectures, ethical governance, cybersecurity integration, and sustainability-oriented digital transformation. A comprehensive literature review identifies emerging trends, research gaps, and practical applications of collaborative AI systems in enterprise environments. The research methodology adopts a qualitative and conceptual research design supported by systematic literature analysis and framework evaluation. Findings indicate that human-centered cloud AI models significantly improve enterprise resilience, collaborative intelligence, innovation capability, operational sustainability, and adaptive decision-making. The study concludes that integrating ethical AI governance, explainable AI, cloud scalability, and human oversight is essential for creating trustworthy and sustainable digital enterprises in the Industry 5.0 era.